IMPROVING STUDENTS’ ABILITY IN WRITING A PARAGRAPH ORIENTATION OF NARRATIVE TEXT THROUGH DICOGLOSS TECHNIQUE - Claudia, Cindy (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe aim of this research was to see the process of improving students’ ability in writing a paragraph orientation of narrative text for the tenth grade students of SMA Santo Fransiskus Asisi Pontianak through Dictogloss technique. The researcher used Classroom Action Research. This research was carried out in two cycles. The observation checklist sheet, field notes, and interview rubric analysis were the instruments to gather the data. The sample of this research was class X C that consisted of 27 students which was chosen by using purposive sampling technique The results in this research indicated that there was an improvement of the students’ ability in writing a paragraph orientation of narrative text. The mean score of writing test 1 was 53.89. After applied Dictogloss technique, the mean score in cycle 1 gained 60.18 and the improvement was 11.67%. Next, the result of the cycle 2 showed that their mean score derived 68.33 and gained 26.79% of improvement. The class condition during teaching learning process was good enough. In addition, there was a positive response from the English teacher and the students about the implementing the action. In conclusion, Dictogloss technique can improve students’ ability in writing a paragraph orientation of narrative text. Keywords :Narrative Text, Writing Ability, Dictogloss Technique.